Understanding placed-based pathways by which housing is related to health inequalities: a qualitative interview study in London - Sheringham, Jessica; Klaptocz, Joanna; Ingram, Elizabeth; Ucci, Marcella (Frontiers in Environmental Health, 2024)
Background Housing is a well-recognised determinant of health. It is not known, however, how local decision makers conceptualise the links between housing and health and, in turn, what opportunities they recognise to intervene to address health inequalities. Materials and methods A qualitative interview study was undertaken in two areas of London with a range of staff working for public services or local voluntary groups who had professional or lived experience of local housing problems. Data were analysed using a conceptual model that articulated how housing may lead to health inequalities. Results Twenty individuals were interviewed, comprising fifteen staff employed by two London Councils and five individuals working in the voluntary sector helping people with housing problems. All participants recognised the importance of structural inequalities in determining access to appropriate quality housing and in influencing the health effects of housing. Overcrowding emerged as a prominent theme, exemplifying the interrelated nature of housing problems. Participants actively considered how the role of public services could alleviate or exacerbate health inequalities. Interventions were often focused specifically on housing and were limited by participants' partial views of the housing-health landscape. Discussion A comprehensive framing of housing as a determinant of health inequities was a relevant lens to conceptualise the relationship between housing and health in London. Integration of policies, services and information is needed to design and implement holistic interventions to address inequalities associated with housing. Future conceptual models to understand the interrelationship between place, housing and health may benefit from explicit consideration of the role of public services.